Evaluation and follow-up of healthy aging and aging with mild cognitive impairment (MCI) through TAVEC. - García-Herranz, Sara; Díaz-Mardomingo, María C.; Peraita, Herminia (Anales de Psicología / Annals of Psychology, 2013)
Mild cognitive impairment (MCI) is defined as an intermediate state between normal aging and disease that can sometimes evolve to Alzheimer´s type dementia (DAT). The need to find markers for the early detection of MCI requires specific neuropsychological tests; basically, memory tests can be considered early markers of this syndrome. This proposed research intends to verify whether the Learning Verbal Test from Spain - Complutense (TAVEC) is useful to assess and follow up subjects to determine whether they are aging healthily or they have MCI, depending on whether their stability or instability is temporary. The sample comprises 179 persons (95 healthy subjects and 84 MCIs) aged between 58-90 years old. The subjects are currently tested twice a week with a TAVEC test along with other neuropsychological tests The results showed significant differences between the first and the second evaluation, which is conducted one year later, re-evaluating the total sample and dividing it into healthy subjects or MCI subjects (stable and unstable). There were differences between different subgroups, classified according to the temporary stability or instability. The TAVEC is a useful tool to evaluate verbal episodic memory in its early stages and to follow up healthy aging and/or MCI.